Work-Related Training and Wages : An Empirical Analysis for Male Workers in Switzerland - Michael Gerfin (Institute for the Study of Labor (IZA), 2004)
Work-related training is considered to be very important for providing the workforce with the necessary skills for maintaining and enhancing the competitiveness of the firms and the economy. On the individual level, the primary effect of training should be an increased productivity of the trained workers. This paper provides estimates of the effects of training on wages which can be seen as a lower bound for the effects on productivity. Based on panel data from the Swiss Labour Force Survey (SLFS) I estimate these effects using nonparametric matching methods. Training is measured either as firm-sponsored training or as any work-related training. The data show that multiple participation in work-related training is not a rare event. This complicates the analysis considerably because the evaluation of dynamic treatments is not yet fully developed. As a solution to this problem a heuristic difference-in-differences approach to estimate the incremental effect of further training events is used. The results indicate that it is important to account for multiple training events. Taken together, there are significant effects of work-related training on wages of roughly 2% for each training event. There is some evidence that workers who already have high earnings profit more from continuous work-related training.
Keywords: C14; J31; I2; 330; Training; Wages; Nonparametric Matching; Berufsbegleitende Ausbildung; Betriebliche Bildungsarbeit; Lohn; Schätzung; Schweiz